Highly efficient multifunctional frosted luminescent solar concentrators with zero-energy nightscape lighting. Issue 41 (6th October 2022) - Zhang, Yi; Zheng, Zida; Cao, Xiudong; Gu, Gangwei; Gan, Zhixing; Huang, Rui; Guo, Yanqing; Hou, Dejian; Zhang, Xiaowei
Abstract : Frosted luminescent solar concentrators exhibit potential as both deployed power-generating and persistent luminescence devices to replace commercial frosted glass. Abstract : Luminescent solar concentrators (LSCs) are receiving increasing attention as photovoltaic (PV) modules to replace glass for seamless integration into the urban architectural landscape. Glass facades exhibiting different transparencies are highly demanded, however, LSCs with similar features of frosted glass are rarely reported. In this work, we developed eco-friendly multifunctional frosted LSCs (FLSCs) by incorporating the Si5.9 Al0.1 O0.1 N7.9 :Eu 2+ phosphor with photoluminescence quantum yield (PLQY) up to 93% and the SrAl2 O4 :Eu 2+, Dy 3+ phosphor with bright persistent luminescence into a thiol–ene polymer. A record-high external quantum efficiency ( η ext ) of 29.8% is demonstrated for a 5 cm × 5 cm FLSC with the corresponding power conversion efficiency (PCE) of 1.37% and optical efficiency ( η opt ) of 3.4% by attaching Si PV cells along the FLSC. The FLSC is proven to be an excellent substitute for commercial frosted glass thanks to its similar aesthetic quality. In addition to PV modules, FLSCs also act as zero-energy nightscape lighting devices due to the persistent luminescence. FLSCs exhibit favorable photostability during 150 h of 1 Sun illumination. Therefore, this work develops a new type of multifunctional and stable FLSC, which can not only replace frosted glass in multiple scenarios, but also play important roles in photovoltaic and lighting applications.